Antenatal Care Counseling for Pregnant Women as an Effort to Prevent Stunting - Simarmata, Vidi Posdo A.; Marlina, Lina; Luhulima, Danny Ernest Jonas; Udjung, Gorga I.V.W; Langi, Louisa Ariantje (Asian Journal of Community Services, 2024)
Antenatal Care aims to prepare the mother and child as well as possible, both and psychologically, as well as to protect them throughout their pregnancies, deliveries, and the postpartum period so that the condition of the mother and child at birth is physically and mentally healthy and normal. The high maternal mortality rate, including during childbirth, is a driving force for the need to provide education or counseling regarding Antenatal Care to pregnant women. With 41 pregnant women from four villages in Jatigede District, Sumedang Regency, West Java, as participants, this community service method employs an educational approach through counseling. Experts in their respective fields serve as resource people in the counseling process. The post-test results were consistent with the counseling's findings, which demonstrated a substantial increase in participants' knowledge.